Las organizaciones sociales urbanas y su relación en la participación ciudadana en el Gobierno Autónomo Descentralizado Municipal del cantón Valencia, año 2013 - Saldarriaga Saldarriaga, Guadalupe Elizabeth (2014)
This research was performed at Valencia county, known as the "Garden of the Rivers” is one of the youngest Ecuador, cantons second extension (971.9 km2). Fertile land for agricultural production. It has a population of 42,556 inhabitants according to the 2010 census. December 13 is the date that marks its independence. It is also considered one of the most neat and clean in the province of Los Ríos cantons. During her years of political life, Valencia has shown that its growth is not due to chance, but is the product of serious work, and to have had real leaders in municipal administration, as the Engineer Setting Strong Troy, his first mayor, and Mr. Juan Carlos currently Troy, the head of the municipal administration, whose motto is "Together We advance the development and progress of Valencia”. However their virtue, The Autonomous Decentralized Municipal Government of Valencia has not complied with the provisions of the Constitution and other related laws regarding Citizen Participation. Hence arises the interest to perform this research, whose overall objective is: To determine the level of citizen participation in the Urban Social Organizations in Decentralized Autonomous Government of the Canton Municipal Valencia, 2013 and consists of the following specific objectives: 1 ) evaluate the compliance with the Urban Social Organizations Citizen Participation in Decentralized Autonomous Government of Valencia county , 2) Research in Urban Social Organizations canton Valencia their level of preparation and knowledge of Citizen Participation , 3) Establish processes for Citizen Participation Decentralized Autonomous Government of Valencia county in 2013 , and 4 ) propose the development of a Motivational Talks Planning for the Municipality of Valencia in the run Social Organizations canton and improve the participation of citizens in the administration city . The following research methods were used: inductive, deductive, analytic and synthetic, plus information extracted from primary sources. The techniques used were: direct observation, interviews and surveys. The population size was determined according to the data provided by the National Institute of Statistics and Census year 2010 and projection for 2013 , bringing the population was determined, and the municipal archives of the number of neighborhood organizations Canton . The result of this research is: Poor administration of the municipal government of the canton Valencia in the implementation of citizen participation as required by law, and as proposed Planning Motivational Talks defined for the local municipality implements the training of community for effective intervention in municipal work.